The Effect of Consumption of Basil Jelly on Vaginal Discharge in Adolescent Women - Siti Yulaikah; Dewi Susilowati; Helmi Nurlaili; Weni Puspita (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2025)
Background : In Indonesia, around 75% of women experience vaginal discharge and 31.8% of teenagers aged 15-24 years. Vaginal discharge is the discharge of liquid from the vaginal opening. Generally, vaginal discharge is clear and odorless. Continuous vaginal discharge will have an impact on reproductive health and can become a serious problem if not treated immediately. One effort to reduce vaginal discharge is to consume basil because it contains cineol, eugenol, anetol, saponins, flavonoids, polyphenols and tannins.Objective : To determine the effect of consuming basil jelly on vaginal discharge in adolescent girls at SMP Negeri 1 Plaosan.Methods : Quasi experiment with a nonequivalent control group design approach. The population is all female students in class IX who are 1-12 days after menstruation. The sampling technique used was purposive sampling of 30 female students. Data processing was carried out using the Mann Whitney test.Results : The description of vaginal discharge before and after treatment experienced the most changes in color, amount of fluid, smell and itching. There is an effect of consuming basil leaves in gelatin form on vaginal discharge, expressed by an Asymp.Sig (2-tailed) value of 0.004.Conclusion : There is an effect of consuming basil jelly on vaginal discharge in adolescent girls.